Canadian Association of Gastroenterology Consensus Guidelines on Safety and Quality Indicators in Endoscopy - David Armstrong; Alan Barkun; Ron Bridges; Rose Carter; Chris de Gara; Catherine Dubé; Robert Enns; Roger Hollingworth; Donald MacIntosh; Mark Borgaonkar; Sylviane Forget; Grigorios Leontiadis; et al. (Canadian Journal of Gastroenterology)
Several organizations worldwide have developed procedure-based guidelines and/or position statements regarding various aspects of quality and safety indicators, and credentialing for endoscopy. Although important, they do not specifically address patient needs or provide a framework for their adoption in the context of endoscopy services. The consensus guidelines reported in this article, however, aimed to identify processes and indicators relevant to the provision of high-quality endoscopy services that will support ongoing quality improvement across many jurisdictions, specifically in the areas of ethics, facility standards and policies, quality assurance, training and education, reporting standards and patient perceptions.